2021
DOI: 10.1002/admt.202000787
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Metamaterials: A Review of Theories, Structures, Fabrication Approaches, and Applications

Abstract: Acoustic metamaterials (AMs), which are materials composed of subwavelength periodic artificial structures with specific designs, have drawn significant research attention. This is because of the extraordinary abilities of AMs to manipulate acoustic waves compared with those of traditional acoustic materials. In this review, current advances in AM research are comprehensively investigated and summarized. First, major theories regarding AMs, including the acoustic wave equation, crystal lattice and energy band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 330 publications
(417 reference statements)
0
57
0
Order By: Relevance
“…Metamaterials are artificially structured materials with atypical effective parameters that are primarily determined by the metamaterials' microstructure instead of chemical composition. Research on acoustic metamaterials, reviewed in [1][2][3], has rapidly grown since the works by Liu et al [4] and Fang et al [5] who reported, respectively, acoustic metamaterials exhibiting negative real part of the effective density and compressibility in a narrow frequency band. In both cases, this is due to the resonant behavior of the metamaterial constituents; with consequences being the existence of sub-wavelength bandgaps (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metamaterials are artificially structured materials with atypical effective parameters that are primarily determined by the metamaterials' microstructure instead of chemical composition. Research on acoustic metamaterials, reviewed in [1][2][3], has rapidly grown since the works by Liu et al [4] and Fang et al [5] who reported, respectively, acoustic metamaterials exhibiting negative real part of the effective density and compressibility in a narrow frequency band. In both cases, this is due to the resonant behavior of the metamaterial constituents; with consequences being the existence of sub-wavelength bandgaps (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the unconventional acoustic behavior is confined to narrow frequency bands. While this limitation could, at least in part, be overcome by visco-thermal losses, it is known that excessive losses can deteriorate the performance of acoustic metamaterials (see, e.g., [3,38]). This clearly points out the need to properly account for losses in the modelling of acoustic metamaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] New physical mechanisms, other than viscous dissipation in the vicinity of the solid surface and heat conduction through solids, were introduced to achieve effective low-frequency sound absorption. 11,12 Acoustic metamaterials are articial structural materials with periodic or non-periodic unit arrangements to obtain local resonance and special intrinsic parameters, 13 such as negative effective mass density, negative effective modulus of elasticity, and zero refractive index. [14][15][16][17][18] These unconventional properties are usually difficult to nd in traditional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic metamaterials (AMs) consisting of subwavelength artificial structures have been widely used to manipulate sound waves with specific requirement and realize many novel functionalities, [1][2][3] such as acoustic cloaking, [4,5] acoustic energy harvesting, [6][7][8] acoustic imaging, [9,10] and so on. In recent years, metasurfaces with subwavelength thickness, as 2D counterparts of metamaterials, have been first proposed via the generalized Snell's law in optics.…”
Section: Introductionmentioning
confidence: 99%